Development of a Module with Comprehensive Intelligence about Fungi Material for Class X SMA/MA - Nurul Amrina Rosada; Ardi Ardi; Helendra Helendra; Relsas Yogica (Bioeducation Journal, 2019)
Quality of education can be realized with the procurement of instructional materials in the form of module in accordance with demands of the curiculum 2013. Module in accordance with the curiculum 2013 containing values of spiritual intelligence, social and emational intelligence, intelctual intelligence and skilfulness intelligence. These four intelligence are known as comprehensive intelligence, but the module wich is contains a comprehensive intelligence valid and practical. This research is design development study that uses a PLOMP method, wich is consisting of three phases: preliminary research, development or prototyping phase, and assesment phase. The research was conducted in SMAN 4 padang with the subject of the research of the students of grade X MIA 1 and grade X MIA 5 SMAN 4 Padang and the object in this research is a module prodct containing comprehensive intelligence about the function material for class X SMA/MA. The data is primary data namely the data obtain directly through questionnaire validity and practicality on the subject of research. From the result of this research, found that the module has a comprehensive intelligence on valid and practical materials, the resulting module is very practical by teachers and learners in terms of language criticism, learning efficiencies and benefits.